Syndemic effects in complex humanitarian emergencies: A framework for understanding political violence and improving multi-morbidity health outcomes - Kohrt, Brandon A. (Soc Sci Med, 2022)
A hallmark of complex humanitarian emergencies is the collective exposure, often over extended periods of time, to political violence in the forms of war, terrorism, political intimidation, repression, unlawful detention, and forced displacement. Populations in complex humanitarian emergencies have higher risks of multiple co-morbidities: mental disorders, infectious diseases, malnutrition, and chronic non-communicable diseases. However, there is wide variation in the health impacts both across and within humanitarian emergencies. Syndemic theory is an approach to conceptualizing disease and social determinants to understand differential patterns of multi-morbidity, elucidate underlying mechanisms, and better design interventions. Syndemic theory, if applied to complex humanitarian emergencies, has the potential to uncover origins of localized patterns of multi-morbidity resulting from political violence and historical inequities. In this paper, we present two case studies based on mixed-methods research to illustrate how syndemic models can be applied in complex humanitarian emergencies. First, in a Nepal case study, we explore different patterns of posttraumatic stress disorder (PTSD) and depression co-morbidity among female former child soldiers returning home after war. Despite comparable exposure to war-related traumas, girl soldiers in high-caste Hindu communities had 63% co-morbidity of PTSD and depression, whereas girl soldiers in communities with mixed castes and religions, had 8% PTSD prevalence, but no cases of PTSD and depression co-morbidity. In the second case study, we explore the high rates of type 2 diabetes during a spike in political violence and population displacement. Despite low rates of obesity and other common risk factors, Somalis in Ethiopia experienced rising cases of and poor outcomes from type-2 diabetes. Political violence shapes healthcare resources, diets, and potentially, this epidemiological anomaly. Based on these case studies we propose a humanitarian syndemic research agenda for observational and intervention studies, with the central focus being that public health efforts need to target violence prevention at family, community, national, and global levels.